PREVENTION OF INFECTIONS ASSOCIATED WITH CENTRAL VENOUS CATHETER IN NEUROTROPENIC PATIENTS - Elaine Drehmer de Almeida Cruz; Ivanete Moreira; Zélia de Fátima Quiquio (Universidade Federal do Paraná, 2000)
Neutropenic patients submitted to chemotherapy and support treatments depend on the appropriate insertion, maintenance and observation of the central venous catheter. Infectious complications represent important risks to patient´s survival and relate to endogenous conditions such as immunosuppresion and to exogenous conditions such as catheter characteristics, technique and insertion site, period of permanence, administered fluids and technical quality of maintenance. This study approaches such questions and describes surveillance and prevention actions provided to patients through nursing assistance plan.